1.68. Rozwiąż nierówności: a) (0, 5) ^ (x ^ 2 – 9x + 17, 5) < 8/(sqrt(2)) 64 b) (0,6)^ * >=2 7 9 e) (0, 8) ^ (2x – 1) >= (1, 25) ^ (x + 2) c) f) (1 1/3) ^ x > 0 ( sqrt[3] 49 81 ) ^ x-4 < ( 7 9 )^ 3x b) (sqrt(2)) ^ |x - 1| < 4 d) (0, 4) ^ (x - 6) <= 2, 5 (2/3) ^ (x + 2) * (3/2) ^ (2x + 1) > (27/8) ^ (x – 3) (1/25) ^ (x – 3) * 5 ^ (2x + 6) <= 625 ^ (1/2 * x - 1) b) d) ((sqrt(2)) ^ (x + 1))/((2 * root(3, 2)) ^ (x + 1)) >= 1/4 (2/3) ^ (2x – 1) * (81/16) ^ (x – 2) <= (2, 25) ^ (4x + 1) (3 ^ (x ^ 2))/((sqrt(3)) ^ (x + 1/2)) >= root(4, 3) (25 ^ (x ^ 2))/((root(4, 5)) ^ (8x)) <= 625/(5 ^ (4x)) b) d) b)

1.68. Rozwiąż nierówności: a) (0, 5) ^ (x ^ 2 – 9x + 17, 5) < 8/(sqrt(2)) 64 b) (0,6)^ * >=2 7 9 e) (0, 8) ^ (2x – 1) >= (1, 25) ^ (x + 2) c) f) (1 1/3) ^ x > 0 ( sqrt[3] 49 81 ) ^ x-4 < ( 7 9 )^ 3x b) (sqrt(2)) ^ |x – 1| < 4 d) (0, 4) ^ (x – 6) <= 2, 5 (2/3) ^ (x + 2) * (3/2) ^ (2x + 1) > (27/8) ^ (x – 3) (1/25) ^ (x – 3) * 5 ^ (2x + 6) <= 625 ^ (1/2 * x – 1) b) d) ((sqrt(2)) ^ (x + 1))/((2 * root(3, 2)) ^ (x + 1)) >= 1/4 (2/3) ^ (2x – 1) * (81/16) ^ (x – 2) <= (2, 25) ^ (4x + 1) (3 ^ (x ^ 2))/((sqrt(3)) ^ (x + 1/2)) >= root(4, 3) (25 ^ (x ^ 2))/((root(4, 5)) ^ (8x)) <= 625/(5 ^ (4x)) b) d) b)

Kliknij aby dołączyć do Akademii Matematyki

Dodaj komentarz